FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - PARHUSIP, POLTAK TEODORUS; PASARIBU, LISBET R. (Jurnal Riset Akuntansi & Keuangan, 2022)
This research aims to determine the factors that affect the timeliness of submitting financial statements listed in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2016 -2017. The factors are Ownership Structure, Debt To Equity Ratio (DER), Return On Asset (ROA), Company Size, Current Ratio (CR). The population used in this research was manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2017. The samples in this study were selected based on the purposive sampling method, which is carried out by taking samples from the population based on a certain criterion adjusted to the goals and problems of the researcher. Samples obtained from 153 manufacturing companies listed on the Indonesia Stock Exchange with observations for two years, so that the selected sample was 67 samples.  The analytical methods used are Descriptive Statistical Analysis, Logistic Regression analysis, Assessing the Overall model (overall model fit), Coefficient of Determination (Nagelkerke R Square), Assessing Feasibility, Regression Model, Classification Table, hypothesis testing. The results of the logistic regression test showed that the adjusted value of R2 was 36.2%, from these results it can be concluded that the ownership structure, debt to equity ratio, return on assets, company size, and current ratio were able to explain punctuality of 36.2%. Simultaneous tests concluded that all independent variables had a significant and positive effect on dependent variables. Partial testing shows the results that the ownership structure and return on assets have a negative and unconscionable effect on the timeliness of submitting financial statements, the debt to equity ratio has a negative and significant effect on the timeliness of submitting financial statements, while the size of the company and the current ratio have a positive and significant effect on the timeliness of submitting financial statements